The long way to an efficient information society – information literacy perceptions among Croatian librarians - Lasić-Lazić, Jadranka (Array, 2006)
Contemporary societies have devised clear strategies towards the development of information societies based on building of stable information and communication infrastructures. But providing access to technologies and making information available is not sufficient. How to develop and utilize knowledge and skills or investigative methods to identify, access, retrieve, and apply relevant content are at the core of realizing the promises and premises of information societies. A crucial pillar for developing these capabilities is information literacy, which focuses on enabling for critical thinking, self-directed learning and the responsible consume of information, each of one necessary for intelligent existence in the information age. Libraries as a part of the educational-informational infrastructure can make a unique and specific contribution to the aspired information literacy agenda. Despite the relevance, potential and impact of information literacy activities on the wider social context, libraries in Croatia are lagging far behind the emerging global information literacy movement. To investigate reasons for this unfavourable constellation, the authors have conducted two surveys among Croatian school and academic librarians, which will be presented in the paper. The gathered results present an important contribution to the articulation of a necessary information literacy agenda.